Competence of The Authority of Military Police Investigators on Money Laundering Criminal Cases in Connection Cases - Sudarma Setiawan; Madiasa Ablisar; Sunarmi Sunarmi; Mahmud Mulyadi (LOCUS MEDIA PUBLISHING, 2023)
The investigation of money laundering cases against connexity cases whose perpetrators are